Induction of Maturogenesis by Partial Pulpotomy: 1 Year Follow-Up - A. Bacaksiz; A. Alaçam (Case Reports in Dentistry)
In cariously exposed immature permanent teeth, the treatment choice is controversial in pediatric dentistry. Radical root canal treatment usually appears to be the solution for these teeth. Even partial pulpotomy is a vital treatment for traumatically exposed immature permanent teeth; extending the borders of indication towards cariously exposed immature permanent teeth with reversible pulpitis may abolish the necessity of pulpectomy. This article describes the partial pulpotomy of a cariously affected immature permanent teeth and the follow-up for 1 year. A healthy 11-year-old male patient was referred to Gazi University Faculty of Dentistry Department of Pediatric Dentistry. The patient had reversible pulpitis symptoms on teeth numbered 45. At radiographic examination, immature apex and deep caries lesion were observed and partial pulpotomy was performed by using calcium hydroxide to maintain vitality of the pulp and allow continued development of root dentin expecting the root will attain full maturity. Clinical and radiographic follow-up demonstrated a vital pulp besides not only closure of the apex (apexogenesis), but also physiologic root development (maturogenesis) after 1 year. Partial pulpotomy is an optional treatment for cariously exposed immature permanent teeth for preserving vitality and physiological root development.